Work Conflict, Stress, and Job Satisfaction: A Study of Bus Crew Employees: Konflik Kerja, Stres, dan Kepuasan Kerja: Sebuah Studi terhadap Karyawan Awak Bus - Cahya, Elit Siendhang; Ubaidillah, Hasan (Indonesian Journal of Law and Economics Review, 2023)
This study aimed to investigate how workload, physical work environment, and work conflict affect job satisfaction, with job stress as a moderating variable, among bus crew employees at PO Pratama Putra. The research design used was quantitative, with a population of 52 employees and a non-probability sampling technique called saturated sampling. Smart PLS 3.2.8 software was used for data analysis. The results showed that workload and physical work environment did not have a significant effect on job satisfaction, while work conflict had a significant effect. However, workload and physical work environment did not have a significant effect on job satisfaction through job stress as a moderating variable, but work conflict did. Furthermore, job stress had a significant effect on job satisfaction. The implications of this study are that employers should prioritize conflict management strategies to enhance job satisfaction, and employees should focus on managing job stress to improve their job satisfaction. Highlights: Work conflict had a significant effect on job satisfaction among bus crew employees, highlighting the importance of conflict management strategies in the workplace. Job stress was found to have a significant effect on job satisfaction, emphasizing the need for employees to focus on managing their stress levels to improve their overall job satisfaction. Workload and physical work environment were not significant predictors of job satisfaction, indicating that employers may need to focus on other factors to improve their employees' job satisfaction.